Piecewise-smooth chebfuns - Pachon, R; Platte, R; Trefethen, L (2010)
Algorithms are described that make it possible to manipulate piecewise-smooth functions on real intervals numerically with close to machine precision. Break points are introduced in some such calculations at points determined by numerical root finding and in others by recursive subdivision or automatic edge detection. Functions are represented on each smooth subinterval by Chebyshev series or interpolants. The algorithms are implemented in object-oriented Matlab in an extension of the chebfun system, which was previously limited to smooth functions on [- 1, 1]. 2009. Published by Oxford University Press on behalf of the Institute of Mathematics and its Applications. All rights reserved.